Essentials of econometrics - Gujarati, Damodar N. (Thousand Oaks, California SAGE, 2022)
Damodar N. Gujarati's classic text is praised for being logically organized and accessible, providing students with an overview of the basics of econometric theory from ordinal logistic regression to time series. The material is introduced in a clear, concise manner, with extensive examples, and a large number of questions and problems at the end of each chapter to test mastery. The Fifth Edition includes new chapters on time series econometrics and panel data econometrics, and new examples throughout. Appendices to the book provide reviews of the statistics needed to understand the econometric theory and practice discussed in the text. Resources for instructors and students are provided on an accompanying website for the book"--
Contents: Chapter 1: The Nature and Scope of Econometrics - - PART 1: The Linear Regression Model: Chapter 2: Basic Ideas of Linear Regression: The Two-Variable Model - - Chapter 3: The Two-Variable Model: Hypothesis Testing - - Chapter 4: Multiple Regression: Estimation and Hypothesis Testing - - Chapter 5: Functional Forms of Regression Models - - Chapter 6: Qualitative or Dummy Variable Regression Models - - PART 2: Regression Analysis In Practice: Chapter 7: Model Selection: Criteria and Tests - - Chapter 8: Multicollinearity: What Happens if Explanatory Variables are Correlated? - - Chapter 9: Heteroscedasticity: What Happens if the Error Variance Is Nonconstant? - - Chapter 10: Autocorrelation: What Happens If Error Terms Are Correlated? - - PART 3: Advanced Topics In Econometrics: Chapter 11: Elements of Time-Series Econometrics - - Chapter 12: Panel Data Regression Models.
Includes bibliographical references and index.
Keywords: Econometrics; Economics -- Statistical methods